Neem Seed Oil Induces Apoptosis in MCF-7 and MDA MB-231 Human Breast Cancer Cells - Sharma, Ramesh (Asian Pac J Cancer Prev, 2017)
BACKGROUND: In traditional Indian medicine, azadirachta indica (neem) is known for its wide range of medicinal properties. Various parts of neem tree including its fruit, seed, bark, leaves, and root have been shown to possess antiseptic, antiviral, antipyretic, anti-inflammatory, antiulcer, antimalarial, antifungal and anticancer activity. MATERIALS AND METHODS: MCF-7 and MDA MB-231 cells were exposed to various concentrations of 2% ethanolic solution of NSO (1-30 µl/ml) and further processed for cell viability, cell cycle and apoptosis analysis. In addition, cells were analyzed for alteration in Mitochondrial Membrane Potential (MMP) and generation of Reactive Oxygen Species (ROS) using JC-1 and DCFDA staining respectively. RESULTS: NSO give 50% inhibition at 10 µl/ml and 20 µl/ml concentration in MCF-7 and MDA MB-231 cells respectively and, arrests cells at G0/G1 phase in both the cell types. There was a significant alteration in mitochondrial membrane potential that leads to the generation of ROS and induction of apoptosis in NSO treated MCF-7 and MDA MB-231 cells. CONCLUSION: The results showed that NSO inhibits the growth of human breast cancer cells via induction of apoptosis and G1 phase arrest. Collectively these results suggest that NSO could potentially be used in the management of breast cancer.